Analisis Yuridis terhadap Tindakan Overclaim Produk Kosmetika Sediaan Sunscreen - Pascal Amadeo Yapputro; Ariawan Gunadi (CV Rewang Rencang, 2024)
Indonesia is a country with high levels of solar radiation, making it essential for its people to protect their skin from sun exposure during daily activities. Generally, people use sunscreen products to shield their skin. Sunscreen is a cosmetic product containing Sun Protection Factor (SPF) and Protection Grade of UVA (PA), which provide protection against sun exposure. Prolonged exposure to the sun can cause negative effects such as skin cancer and redness, increasing the demand for sunscreen products among the public. With the significant demand for sunscreen, many businesses are selling these products. To attract customers and boost sales, businesses often use advertising as a marketing strategy. However, an issue has arisen in the marketing of these products—businesses engaging in overclaim practices. Overclaim refers to the act of exaggerating the benefits of a product, presenting claims that do not align with the product's actual properties. Such practices violate consumer rights and can harm consumers. Currently, consumer protection is regulated by Law No. 8 of 1999 on Consumer Protection. Articles 7 to 17 of this law prohibit overclaim practices, as they constitute deception toward consumers. Advertising that involves overclaiming may result in consumer losses. Furthermore, in accordance with the law, businesses are required to take responsibility for any harm caused to consumers due to overclaim practices. The adverse effects of overclaiming may lead to a mismatch between the consumer's skin type and the ingredients in the sunscreen product.